Large-scale measurement of urban streets’ space health based on the spatial disorder theory—A case study on the old urban area of Daoli District of Harbin City - Wan, Ting; Wang, Mingxue (Frontiers in Environmental Science, 2023)
As an essential part of urban public space, the basic framework of urban pattern and the human landscape of the city, street space is of great significance to the urban development. From the perspective of urban living safety, the demand of urban space for health has been considered in depth again. Therefore, with emerging new issues in the post-urbanization period, such as the development of public health and slow traffic transportation, street space becomes disordered, and the health of street space has drawn great attention. This paper takes the old urban area of Daoli District of Harbin City as an example. The spatial disorder degree of different streets in the old urban area of Daoli District of Harbin City is derived by using the off-site built environment audit method and mean square weight analysis and other technical methods with multi-source data, such as Baidu map API. In this paper, the spatial health measurement of streets with different properties of land usage in the old urban area of Daoli District of Harbin City is classified, and the classification strategies are proposed based on the calculation results. Based on the theory of spatial disorder, a large-scale measurement of the street space health provides insights and references for the practical urban management in the future. In terms of theoretical research, this paper attempts to fill the gap of urban geospatial disorder research in China.